The influence of incentives on community health worker motivation in the provision of family planning. A case of Msalala and Shinyanga Districts, Tanzania - Maryse Kok; Scholastica Lucas; Josiah Otege; Zando Mkwazu; Ingrid Zuleta; Eefje Smet; Frida Ngalesoni (AOSIS, 2021)
Community health workers (CHWs) are essential in the provision of a wide range of services, including family planning. In Tanzania, deployment of CHWs has largely been supported by non-governmental organizations (NGOs) who often determine their incentives. A mix of incentives is required to increase CHW motivation and, ultimately, performance. This qualitative study aimed to explore how incentives influence CHW motivation in the provision of family planning services in Msalala and Shinyanga districts. The study included focus group discussions and in-depth interviews with 21 CHWs, 12 supervisors and eight policy makers and NGO representatives. Transcripts were coded and narratives were written on types of incentives, motivating and demotivating factors. The study revealed that although CHW motivation was related to feelings of accomplishment and respect from the community, financial incentives were found equally important for motivation. While most CHWs received non-financial incentives, CHWs had unequal access to financial incentives. Key informants confirmed that there was no coordination on incentives at district level. Some CHWs reported demotivation because of misconceptions and unacceptance of family planning in the community and irregular supply of contraceptives. Results from this study show that motivation of voluntary CHWs in Msalala and Shinyanga districts is currently sub-optimal, because of inequity in access to (financial) incentives. There is a need for better coordination and standardization of CHW incentives. Advocacy is needed to increase funding for CHWs' deployment and remuneration. This would increase CHW motimotivation and ultimately performance, also in the field of family planning.